Combining Marketing Strategy Of Word Of Mouth And Mix: The Existence Of Home Businesses Kembang Rose - Retnowati, May Shinta (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2026)
A home-based business (Home Industry) is a type of enterprise that operates mainly from home, often started with limited capital and offering time flexibility as well as lower operational costs, covering various sectors such as culinary, digital services, crafts, and online trade, making it a popular solution for SMEs to add income or become a primary source of income. The home Industry rose flower industry is a local product that has become an icon of a certain area. This product has its own appeal, such as uniqueness linked to the area and a marker for those who have visited that region. In order for the product to be known, there is an important role for strategies in introducing the product. The purpose of this research is to present strategies that are commonly used. This study uses qualitative research by conducting interviews and questionnaires with an in-depth Likert scale, and the analysis used is descriptive statistics. The results of this study indicate that WOM strategies and the marketing mix serve as a combination in carrying out marketing strategies so that products can be recognized by a wide range of audiences. This research has proven that this combination successfully makes the product widely known (brand awareness). Future research may test the combination of WOM and the marketing mix that shows the right and effective measures in driving the audience to the purchase decision stage (conversion) or even brand loyalty.